Textual and non-textual communication in exhibitions – a comparative study of the Pitt Rivers Museum - Chen, Hailin (2024)
The Pitt-Rivers Museum (PRM) in Oxford is a special museum that communicates through its typological displays, whose exhibitory layout can be studied by defining two opposite formats of exhibitions. The first is the textual, like how texts are organised in the writing process. The second is the non-textual, as in how narratives are embedded in a space by focusing on body experience. The two formats provide a basis for understanding how the difference in communication in the museum is generated and how the visitor experience is thereby affected. This research aims to reveal the role of textual and non-textual communications and verify both in the context of the detailed case study of PRM.